A systematic review of the neural correlates of sexual minority stress: towards an intersectional minority mosaic framework with implications for a future research agenda. Issue 1 (31st December 2022) - Nicholson, Andrew A.; Siegel, Magdalena; Wolf, Jakub; Narikuzhy, Sandhya; Roth, Sophia L.; Hatchard, Taylor; Lanius, Ruth A.; Schneider, Maiko; Lloyd, Chantelle S.; McKinnon, Margaret C.; Heber, Alexandra; Smith, Patrick; et al.
ABSTRACT: Background: Systemic oppression, particularly towards sexual minorities, continues to be deeply rooted in the bedrock of many societies globally. Experiences with minority stressors (e.g. discrimination, hate-crimes, internalized homonegativity, rejection sensitivity, and microaggressions or everyday indignities) have been consistently linked to adverse mental health outcomes. Elucidating the neural adaptations associated with minority stress exposure will be critical for furthering our understanding of how sexual minorities become disproportionately affected by mental health burdens. Methods: Following PRISMA-guidelines, we systematically reviewed published neuroimaging studies that compared neural dynamics among sexual minority and heterosexual populations, aggregating information pertaining to any measurement of minority stress and relevant clinical phenomena. Results: Only 1 of 13 studies eligible for inclusion examined minority stress directly, where all other studies focused on investigating the neurobiological basis of sexual orientation. In our narrative synthesis, we highlight important themes that suggest minority stress exposure may be associated with decreased activation and functional connectivity within the default-mode network (related to the sense-of-self and social cognition), and summarize preliminary evidence related to aberrant neural dynamics within the salience network (involved in threat detection and fear processing) and the central executive network (involved in executive functioning and emotion regulation). Importantly, this parallels neural adaptations commonly observed among individuals with posttraumatic stress disorder (PTSD) in the aftermath of trauma and supports the inclusion of insidious forms of trauma related to minority stress within models of PTSD. Conclusions: Taken together, minority stress may have several shared neuropsychological pathways with PTSD and stress-related disorders. Here, we outline a detailed research agenda that provides an overview of literature linking sexual minority stress to PTSD and insidious trauma, moral affect (including shame and guilt), and mental health risk/resiliency, in addition to racial, ethnic, and gender related minority stress. Finally, we propose a novel minority mosaic framework designed to inform future directions of minority stress neuroimaging research from an intersectional lens. HIGHLIGHTS: Minority stress exposure may be associated with alterations within intrinsic connectivity networks. There currently exists a limited number of neuroimaging studies directly investigating the neural correlates of minority stress. Here, we propose a novel minority mosaic framework .